2010
DOI: 10.1051/0004-6361/201014982
|View full text |Cite
|
Sign up to set email alerts
|

HST and VLT observations of the neutron star 1E 1207.4–5209

Abstract: The peculiar central compact object 1E 1207.4−5209 in the G296.5+10.0 supernova remnant has been proposed to be an "antimagnetar" -a young neutron star born with a weak dipole field. Accretion, possibly of supernova fallback material, has also been invoked to explain a large surface temperature anisotropy as well as the generation of peculiar cyclotron absorption features superimposed on its thermal spectrum. Interestingly enough, a faint optical/infrared source was proposed as a possible counterpart to 1E 120… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…Accretion luminosity of magnitude ≈0.1ṁc 2 = 9×10 32 erg s −1 , comparable to the observed luminosity, is then strongly excluded by the absence of such a timing solution. In support of this conclusion, deep Hubble Space Telescope limits on an optical counterpart to 1E 1207.4−5209 (De Luca et al 2011) indicate that the accretion rate of any disk surrounding the NS should be <10 12 g s −1 . It would be straightforward to determine a unique timing solution, but only with a program of phase-coherent timing similar to those we have carried out for the other CCO pulsars.…”
Section: Discussionmentioning
confidence: 82%
“…Accretion luminosity of magnitude ≈0.1ṁc 2 = 9×10 32 erg s −1 , comparable to the observed luminosity, is then strongly excluded by the absence of such a timing solution. In support of this conclusion, deep Hubble Space Telescope limits on an optical counterpart to 1E 1207.4−5209 (De Luca et al 2011) indicate that the accretion rate of any disk surrounding the NS should be <10 12 g s −1 . It would be straightforward to determine a unique timing solution, but only with a program of phase-coherent timing similar to those we have carried out for the other CCO pulsars.…”
Section: Discussionmentioning
confidence: 82%
“…Incidentally, Gotthelf & Halpern (2007) argued that the slow spin and weak magnetic field of 1E 1207 make it possible for accretion from a debris disc left over after the supernova. However, recent optical and infrared observations of 1E 1207 place strong limits on this disc, including a (model‐dependent) estimate of the initial and current total disc mass of ≲10 −6 and ≲10 −10 M ⊙ , respectively (De Luca et al 2011), which implies that the magnetic field could only be buried to a maximum density of ∼10 11 g cm −3 .…”
Section: Discussionmentioning
confidence: 99%
“…Gotthelf & Halpern (2009) reported the discovery of pulsations with a periodicity of 112 ms and very peculiar emission properties. Several studies have been conducted to determine the proper motion of RX J0822-4300 (Hui & Becker 2006a;Winkler & Petre 2007;de Luca et al 2011;Becker et al 2012). Based on data spanning a time baseline of more than ten years, Becker et al (2012) concluded that the CCO has a proper motion of about 71 mas yr −1 , which for a distance of 2 kpc implies a recoil velocity of about 670 km s −1 and an age of 4450 yr for the SNR.…”
Section: Introductionmentioning
confidence: 99%